Are lasers superior to lights in the photoepilation of Fitzpatrick V and VI skin types? – A comparison between Nd:YAG laser and intense pulsed light. (4th July 2017) - BS, Bibilash; Chittoria, Ravi Kumar; Thappa, Devinder Mohan; Mohapatra, Devi Prasad; MT, Friji; S, Dineshkumar; Pandey, Sandhya
ABSTRACT: Background and objectives : There are no large volume comparative studies available to compare the efficacy of lasers over lights for hair removal in Fitzpatrick V and VI skin types. This study is designed to compare the efficacy of Nd:YAG laser versus IPL in the darker skin types.Study design/materials and methods : Thirty-nine patients included in Group-1 were treated with Nd:YAG and 31 in Group-2 with IPL. Both groups received 5 sessions of treatment. The hair counts were assessed using digital photography and manual counting method before and after treatment and the results were analysed. Patient satisfaction scores and pain scores were recorded in each session and compared.Results : Mean hair reduction in the IPL group was 25.70 and Nd:YAG group was 24.12 (95% CI). In the Nd:YAG group, 59% of subjects had burning sensation while the figure was 32.3% in IPL group. Burning was less in IPL group ( p < 0.023). There were no statistically significant differences noticed regarding hyperpigmentation in both the groups ( p < 0.115).Conclusion : Both Nd:YAG and IPL are equally effective for epilation of the darker skin types. Nd:YAG is associated with mild burning sensation in a significant number of patients. Patient satisfaction scores were comparable in both the groups.